2001
DOI: 10.2337/diacare.24.11.1923
|View full text |Cite
|
Sign up to set email alerts
|

Good Metabolic Control Is Associated With Better Quality of Life in 2,101 Adolescents With Type 1 Diabetes

Abstract: OBJECTIVE -It is unclear whether the demands of good metabolic control or the consequences of poor control have a greater influence on quality of life (QOL) for adolescents with diabetes. This study aimed to assess these relations in a large international cohort of adolescents with diabetes and their families.RESEARCH DESIGN AND METHODS -The study involved 2,101 adolescents, aged 10 -18 years, from 21 centers in 17 countries in Europe, Japan, and North America. Clinical and demographic data were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
251
13
20

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(324 citation statements)
references
References 25 publications
40
251
13
20
Order By: Relevance
“…Ethnicity had a greater impact than SES on HbA 1c , and moderate to severe hypoglycaemia was more prevalent in minority ethnic groups and was not associated with SES. These findings are consistent with previous reports that children from ethnic minorities have higher HbA 1c levels in both the USA [2,13,30] and Europe [15,16]. However these differences have often been ascribed to differences in SES [2,18].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ethnicity had a greater impact than SES on HbA 1c , and moderate to severe hypoglycaemia was more prevalent in minority ethnic groups and was not associated with SES. These findings are consistent with previous reports that children from ethnic minorities have higher HbA 1c levels in both the USA [2,13,30] and Europe [15,16]. However these differences have often been ascribed to differences in SES [2,18].…”
Section: Discussionsupporting
confidence: 93%
“…Although data in childhood are limited, poor metabolic control tracks through adolescence and, in turn, HbA 1c in adolescence is strongly correlated with later adult diabetes-related outcome [10][11][12]. Cross-sectional studies typically show that children of ethnic minorities have higher HbA 1c levels [13][14][15][16]. However, it remains unclear whether this poorer metabolic control is independent of SES, and many of the studies examined selected cohorts that may not be representative of the general population [2,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The DQOL is a disease-specific measure designed specifically for use in DCCT but with applicability to a wider range of people with type 1 diabetes [32]. The relation between QOL and metabolic control is controversial [13,[41][42][43][44]. Some studies reported an association between QOL and metabolic control [41,42], whereas others found no association [13,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…A study of healthy children (Bernier et al 2010) also demonstrated similar correlations between BMI percentile and overall body esteem (r ¼ À0.36 to À0.45, p < 0.01); however, those children demonstrated a negative correlation between BMI percentile and scores on the ChEAT (r ¼ À0.22 to À28, p < 0.01). When comparing to patients with chronic metabolic disease, previous research involving patients with Type I diabetes has noted that body dissatisfaction is associated with poor glycemic control, whereas good metabolic control is linked to better quality of life (Meltzer et al 2001;Hoey et al 2001). Poor metabolic control in GSD leads to greater complications and comorbid factors including hypoglycemic episodes, hepatomegaly, hyperlipidemia, hyperlactatemia, nephropathy, and hepatic adeno-mas, which may negatively impact quality of life.…”
Section: Discussionmentioning
confidence: 99%